2014
DOI: 10.1128/aac.01851-13
|View full text |Cite
|
Sign up to set email alerts
|

Histatin 5-Spermidine Conjugates Have Enhanced Fungicidal Activity and Efficacy as a Topical Therapeutic for Oral Candidiasis

Abstract: Oropharyngeal candidiasis (OPC) is caused by the opportunistic fungi Candida albicans and is prevalent in immunocompromised patients, individuals with dry mouth, or patients with prolonged antibiotic therapies that reduce oral commensal bacteria. Human salivary histatins, including histatin 5 (Hst 5), are small cationic proteins that are the major source of fungicidal activity of saliva. However, Hsts are rapidly degraded in vivo, limiting their usefulness as therapeutic agents despite their lack of toxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…AMPs have many potential uses in treatment of complex infections, and their mode of action can be exploited for the generation of novel antifungal molecules. Various applications of human and nonhuman AMPs show the effectiveness of small peptides against the human-pathogenic fungus C. albicans (62,83,86,87). Recently, different AMP resistance mechanisms that allow C. albicans to become either a successful commensal or a human fungal pathogen were discovered (15, 17, 54-56, 61, 88).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPs have many potential uses in treatment of complex infections, and their mode of action can be exploited for the generation of novel antifungal molecules. Various applications of human and nonhuman AMPs show the effectiveness of small peptides against the human-pathogenic fungus C. albicans (62,83,86,87). Recently, different AMP resistance mechanisms that allow C. albicans to become either a successful commensal or a human fungal pathogen were discovered (15, 17, 54-56, 61, 88).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an Hst 5-spermidine conjugate has been developed, which enhanced fungicidal activity compared to nonconjugated Hst 5 (83). It is known that Hst 5 utilizes the polyamine transporters Dur3 and Dur31 for its uptake in C. albicans (16); therefore, the Hst 5 peptide (Hst 5 with amino acids 4 to 15 [Hst 5 [4][5][6][7][8][9][10][11][12][13][14][15] ]) conjugated with a GGG linker and spermidine was rapidly taken up, leading to higher in vitro and in vivo candicidal activity than with nonconjugated Hst 5 (83). Collectively, these results suggest that the development and investigation of AMP conjugates could lead to promising new antifungals.…”
Section: Amps: New Antifungal Agents For Therapy?mentioning
confidence: 99%
“…Thus, C. albicans cells in the oral environment that better transport and accumulate Hst 5 (due to activation of Cek1 MAPK) are likely to have even higher sensitivity to Hst 5 than those in in vitro conditions. In this regard, we found that increasing in vitro killing of Hst 5 conjugates by 50% resulted in a more than four-log-fold reduction in fungal tongue burden in murine oropharyngeal candidiasis (OPC) (33). Similar animal experiments are needed to test the effects of Cek1 activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…7C). To examine the dynamics of early uptake of Hst 5 in cells exposed to P-Cek1 conditions, we measured propidium iodide (PI) uptake visualized by time-lapse confocal microscopy since intracellular PI is a measure of cell death and directly relates to levels of intracellular Hst 5 (33). C. albicans pretreated with GlcNAc at 37°C showed 21% PI-positive cells after 6 min, compared with only 7% PI-positive cells for those cells pretreated with Glc at 30°C (Fig.…”
Section: Figmentioning
confidence: 99%
“…It has recently been shown that cellular uptake is enhanced by conjugation of the active fragment of Hst 5 (shown outlined by a broken line in Fig. 1) with the polyamine spermidine at either the N or C terminus (39). These conjugates were highly effective as topical therapeutics in a murine model of oral candidiasis compared to the original peptide.…”
Section: Binding and Uptake Of Hstmentioning
confidence: 97%